Pharmacokinetics, metabolite profiling, safety, and tolerability of inhalation aerosol of 101BHG-D01, a novel, long-acting and selective muscarinic receptor antagonist, in healthy Chinese subjects - Gao, Huaye; Li, Jintong; Chen, Xiaoping; Sun, Zhanguo; Cui, Gang; Cheng, Minlu; Ding, Li (Frontiers in Pharmacology, 2022)
101BHG-D01 is a novel, long-acting, selective muscarinic receptor antagonist for the treatment of chronic obstructive pulmonary disease (COPD). A single-site, randomized, double-blind, placebo-controlled and dose-escalation study of 101BHG-D01 inhalation aerosol was conducted to evaluate its pharmacokinetics, metabolite profiling, safety and tolerability following the single inhaled doses ranged from 20 μg to 900 μg in healthy Chinese subjects. After inhalation, 101BHG-D01 was absorbed rapidly into plasma with the time to maximum concentration about 5 min, and eliminated slowly with the terminal phase half-life about 30 h. The cumulative excretion rates of 101BHG-D01 in feces and urine were about 30% and 2%, respectively, which showed the study drug was mainly excreted in feces. The maximum drug concentration and area under the plasma concentration-time curve increased with dose escalation in the range of 20 μg to 600 μg, but their values increased out of proportion to the whole studied doses. The main metabolic pathways were loss of phenyl group and hydroxylation. No metabolite that presented at greater than 10 percent of total drug-related exposure was observed. 101BHG-D01 was safe and well tolerated after administration. The study results indicate that 101BHG-D01 is a good candidate for the treatment of COPD and enable further clinical development in subsequent studies in patients.